Linker length affects photostability of protein-targeted sensor of cellular microviscosity. (10th October 2019) - Kubánková, Markéta; Chambers, Joseph E; Huber, Roland G; Bond, Peter J; Marciniak, Stefan J; Kuimova, Marina K
Abstract: Viscosity sensitive fluorophores termed 'molecular rotors' represent a convenient and quantitative tool for measuring intracellular viscosity via Fluorescence Lifetime Imaging Microscopy (FLIM). We compare the FLIM performance of two BODIPY-based molecular rotors bound to HaloTag protein expressed in different subcellular locations. While both rotors are able to penetrate live cells and specifically label the desired intracellular location, we found that the rotor with a longer HaloTag protein recognition motif was significantly affected by photo-induced damage when bound to the HaloTag protein, while the other dye showed no changes upon irradiation. Molecular dynamics modelling indicates that the irradiation-induced electron transfer between the BODIPY moiety and the HaloTag protein is a plausible explanation for these photostability issues. Our results demonstrate that binding to the targeted protein may significantly alter the photophysical behaviour of a fluorescent probe and therefore its thorough characterisation in the protein bound form is essential prior to any in vitro and in cellulo applications.